A multi-physics and multi-time scale approach for modeling fluid–solid interaction and heat transfer. (February 2016) - Bordère, S.; Caltagirone, J.-P.
Highlights: We formulate a unified equation for fluid flow and elastic solid deformation. The formulation allows a monolithic resolution of fluid–structure interaction. Mechanical and heat equations are both formulated with velocity and flux variables. The formulation can model either acoustic or long time scale thermo-mechanics. Elastic wave propagation is modeled in fluid and elastic solid system. Abstract: A novel non-conservative formulation for equations governing thermo-mechanical phenomena is developed to address multi-material and multi-physics issues. The first key point is that this formulation achieves a unifying equation for compressible viscous fluid flow and elastic solid deformation. The second is that the thermo-mechanical equations are both written with velocity and thermal flux variables to solve them simultaneously. With that formulation, interaction conditions at the fluid–structure interface become implicit and state equation is no longer necessary. Multi-time scale problems are solved, from the time scale of acoustic and thermoacoustic wave propagation, to longer time scale of fluid flow and thermal diffusion.